A study of auxiliary factors for judges in sentencing dangerous driving offenses – the mediating role of favorable and unfavorable factors - Liu, Chengjie; Miao, Ziyu; Wang, Ting (Frontiers in Psychology, 2023)
This paper investigates the ancillary factors judges consider when sentencing dangerous driving offenses. These factors are divided into favorable (i.e., “Confess” [CF], and “Actively compensate and obtain forgiveness from victims” [AC]) and unfavorable categories (i.e., “Mainly or solely responsible for the accident” [MSR], and “Post-accident behavior” [BAA]). Results indicate that both types of factors mediate the relationship between “Blood Alcohol Concentration” (BAC) and the sentencing outcome: favorable factors have a significant negative correlation with sentences, while unfavorable ones show a positive correlation. The mediation effect ratios are 13.8% and 19.1% respectively, with no significant differences between their impacts on judges’ sentencing decisions.